2023
DOI: 10.1007/s00431-022-04786-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of ECG parameters after BNT162b2 vaccine in the senior high school students

Abstract: The purpose of this study is to determine the ECG parameter change and the efficacy of ECG screening for cardiac adverse effect after the second dose of BNT162b2 vaccine in young population. In December 2021, in cooperation with the school vaccination system of Taipei City government, we performed a ECG screening study during the second dose of BNT162b2 vaccines. Serial comparisons of ECGs and questionnaire survey were performed before and after vaccine in four male-predominant senior high schools. Among 7934 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…In Taiwan, researchers conducted an interesting study, in which they compared ECGs before and after the second BNT162b2 dose in 4928 senior high school students (12-18 years). 29 They found significant post-vaccination ECG changes in 51 (1%) students, mostly asymptomatic. Alterations included ST-T changes, premature ventricular contractions (PVC), sinus bradycardia, atrial tachycardia, incomplete right bundle branch block, QRS axis change, and mild QT prolongation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Taiwan, researchers conducted an interesting study, in which they compared ECGs before and after the second BNT162b2 dose in 4928 senior high school students (12-18 years). 29 They found significant post-vaccination ECG changes in 51 (1%) students, mostly asymptomatic. Alterations included ST-T changes, premature ventricular contractions (PVC), sinus bradycardia, atrial tachycardia, incomplete right bundle branch block, QRS axis change, and mild QT prolongation.…”
Section: Discussionmentioning
confidence: 94%
“…The authors concluded that the incidence of clinical and even subclinical myocarditis was low in BNT162b2 vaccine recipients, and that the BNT162b2 vaccine is unlikely to cause life-threatening arrhythmia in healthy young individuals. 29 Hopefully, lay people and medical professionals will rely on verified and properly analysed data to arrive at substantiated conclusions regarding vaccination effects in the years to come. Himelfarb and colleagues have, among others, delineated the consequences of COVID-19 misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of arrhythmia and myocarditis was 0.1%, which means that the most severe manifestations have a frequency of 1 in 1000. The authors mention that the cost of assessing the mRNA-induced adverse events at the cardiac level should stimulate discussion [ 86 ].…”
Section: Safety Of Covid-19 Vaccines In People With Autoimmunity and ...mentioning
confidence: 99%
“…A large study enrolling 7934 high school students after mRNA vaccination and ECG screening revealed that the second dose of anti-SARS-CoV-2 vaccination with a mRNA-based vaccine can have significant cardiac adverse effects. Thus, among 4928 eligible study participants, 763 students (17.1%) had at least one cardiac symptom (mostly chest pain and palpitation); abnormal ECG changes were obtained in 51 subjects (1.0%), of whom one was diagnosed with mild myocarditis whereas four were judged to have significant arrhythmia [ 89 ]. Similarly, very low rates of post-vaccination arrhythmias (about 0.2–1.0%) were observed in a UK study of over 38 million people who received a COVID-19 vaccine, but relatively higher rates were seen in those who had been tested SARS-CoV-2 positive [ 90 ].…”
Section: Covid-19 Vaccination-associated Arrhythmiasmentioning
confidence: 99%